From Plants to Psycho-Neurology: Unravelling the Therapeutic Benefits of Bioactive Compounds in Brain Disorders - Clara Grosso; Marlene Santos; M. Fátima Barroso (MDPI AG, 2023)
The brain's sensitivity to oxidative stress and neuronal cell death requires effective pharmacotherapy approaches. Current pharmacological therapies are frequently ineffective and display negative side effects. Bioactive chemicals found in plants may provide a potential alternative due to their antioxidant and neuroprotective properties and can be used in therapy and the management of a variety of neuropsychiatric, neurodevelopmental, and neurodegenerative illnesses. Several natural products, including vitamin C, Cammelia sinensis polyphenols, Hypericum perforatum, and Crocus sativus have shown promise in lowering oxidative stress and treating symptoms of major depressive disorder (MDD). Similarly, bioactive compounds such as curcumin, luteolin, resveratrol, quercetin, and plants like Acorus gramineus, Rhodiola rosea, and Ginkgo biloba are associated with neuroprotective effects and symptom improvement in neurodevelopmental disorders such as autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (ADHD). Furthermore, in neurodegenerative diseases, natural compounds from Rhodiola rosea, Morinda lucida, and Glutinous rehmannia provide neurological improvement. Further study in clinical samples is required to thoroughly investigate the therapeutic advantages of these bioactive substances for persons suffering from these illnesses.